Spanish Validation of the Long and Short Versions of the Problematic Pornography Consumption Scale (PPCS and PPCS-6) in Adolescents - Villena-Moya, Alejandro; Granero, Roser; Chiclana Actis, Carlos; Potenza, Marc N.; R. Blycker, Gretchen; Demetrovics, Zsolt; Bőthe, Beáta; Steward, Trevor; Fernández-Aranda, Fernando; Jiménez-Murcia, Susana; Mestre-Bach, Gemma (Archives of Sexual Behavior, 2024)
Although 1–14% of adolescents may experience problematic pornography use (PPU), psychometrically sound instruments for assessing PPU in Spanish-speaking adolescents are scarce. Given the advantages of the different forms of the Problematic Pornography Consumption Scale (PPCS), the aim of the present study was to assess the psychometric properties of the PPCS and PPCS-6, and to examine associations between PPU and age among boys and girls. Two school-based adolescent samples were recruited in Spain (n = 650; Mage = 16.0 [SD = 1.1]; 50% girls and 50% boys) and Mexico (n1, 160; Mage = 15.8 [SD = 1.1]; 68% girls) to assess the psychometric properties of the PPCS and PPCS-6. Confirmatory factor analysis was applied and convergent and discriminant validity with other measures related to PPU was also tested. The results provided empirical support for the six-factor structure of the PPCS and the one-factor structure of the PPCS-6. Boys with older age showed higher levels of tolerance than girls on the PPCS in both countries. Both the PPCS and the PPCS-6 may be considered valid psychometric instruments for the assessment of PPU in Spanish-speaking adolescents from Spain and Mexico.
Keywords: compulsive sexual behavior; sexually explicit material; addictive behaviors; compulsive behaviors; problematic pornography use; adolescents; Scopus; JCR